2019
DOI: 10.1002/jmri.26612
|View full text |Cite
|
Sign up to set email alerts
|

Patient respiratory‐triggered quantitative T2 mapping in the pancreas

Abstract: Background Long acquisition times and motion sensitivity limit T2 mapping in the abdomen. Accelerated mapping at 3 T may allow for quantitative assessment of diffuse pancreatic disease in patients during free‐breathing. Purpose To test the feasibility of respiratory‐triggered quantitative T2 analysis in the pancreas and correlate T2‐values with age, body mass index, pancreatic location, main pancreatic duct dilatation, and underlying pathology. Study Type Retrospective single‐center pilot study. Population Eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…T1 and T2 relaxation times are valuable as quantitative parameters to characterize different tissues, especially in myocardial and liver diseases (Apprich et al, 2012;Kali et al, 2015;Blystad et al, 2017;Chen et al, 2017;Vietti Violi et al, 2019). T1 mapping was shown to improve the diagnosis of myocarditis, infarction, iron overload, and amyloidosis (Guo et al, 2009;Karamitsos et al, 2013;Kali et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…T1 and T2 relaxation times are valuable as quantitative parameters to characterize different tissues, especially in myocardial and liver diseases (Apprich et al, 2012;Kali et al, 2015;Blystad et al, 2017;Chen et al, 2017;Vietti Violi et al, 2019). T1 mapping was shown to improve the diagnosis of myocarditis, infarction, iron overload, and amyloidosis (Guo et al, 2009;Karamitsos et al, 2013;Kali et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The MRF framework allows qualitative and quantitative data to be acquired simultaneously, allowing ready comparison between longitudinal time points and against population-derived norms, as well as giving improved imaging repeatability and more meaningful interpretation of intensity changes. The total acquisition time was very low when compared with other reported single parameter acquisitions (non-MRF based), which include quantitative T 2 measurements of the pancreas at 1.5 T: 8 min 16 and 3 T: 2 min 50 s 9 . Similar to Wang 35 , T 1 maps with MRF were obtained in 10 s/slice, although we did Figure 3.…”
Section: Discussionmentioning
confidence: 89%
“…Endoscopic ultrasonography (EUS) is the most sensible imaging method for the pancreas 3,4 , but it is invasive, operator dependent and associated with complications. T 1 and T 2 relaxation times are valuable quantitative parameters to characterize different tissues, particularly in the assessment of myocardial and liver diseases [5][6][7][8][9] . Thus far only some studies have reported on the value of quantitative MRI on the pancreas.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In consequence, this would prolong the scan time far beyond what is clinically acceptable, compromising the applicability of our approach. In addition, the proposed T 2 mapping strategy has been proved to deliver maps in agreement with conventional techniques and with excellent reproducibility, as well as good sensitivity toward T 2 alterations caused by pathologies . Lastly, it should be noted that fitting errors leading to an inaccurate estimation of T 1 and T 2 values were not discussed here, because these can be found in the original publications …”
Section: Discussionmentioning
confidence: 96%